Triarylamine-BODIPY derivatives: A promising building block as hole transporting materials for efficient perovskite solar cells. (December 2019) - Ortiz, Alejandro
Abstract: In this work, the syntheses and characterization of four new TPA-BODIPY dyads as hole-transporting layers (HTLs) are reported. The photophysical and electrochemical properties of the dyadsBTPA-I, BTPA-II, BTPA-III andBTPA-IV are investigated in solution and compared with the reference compoundsBDP, BDP1, BDP2, TPA, A (triphenylamine) andB (4, 4′-dimethoxitriphenylamine). The TPA-BODIPY derivatives strongly absorb visible light and upon photoexcitation at the BODIPY unit, these dyads undergo photoinduced electron transfer to form the corresponding charge-separated species, which was confirmed by solvatochromic measures of fluorescence. Their redox potentials and photophysical properties suggested that the newBTPAs derivatives showed a better ionization potential that free triphenylamines, which makes them promising candidates to use as hole transport layers (HTLs). Highlights: A facile synthetic route for BODIPY-Triarylamine dyes with non-conventional electronic and optical properties. The BODIPY-Triarylamine dyes undergo photoinduced electron transfer to form the corresponding charge-separated species. The new synthesized compounds appear as promising candidates to use as hole transport layers (HTLs).